LEXICAL VARIATION IN UNIVERSITY STUDENTS’ ACADEMIC WRITING - M. Aries Taufiq; Rahmi Eka Putri; Resti Amalia; Ririn Septia; Hidayati; Asmawati (Edutainment, 2024)
Lexical variation demonstrates word variations utilized in university students’ writing. The focus of this study was to investigate the lexical variation in students’ academic writing and factors contributing to the variations in their’ writing. The data sources for this descriptive study were the introduction portions of the thesis proposals submitted by the students. To identify lexical variance in students' writing, thirty introduction portions from their thesis proposals were gathered and examined. The results showed that university students used fewer different terms in their writing and that nouns predominated in their compositions. Furthermore, the morphological knowledge gaps and vocabulary knowledge of the students were the elements impacting the lexical variations in their academic writing. This study came to the conclusion that pupils were still unable to use a variety of terms in their writing based on its findings. Therefore, it was anticipated that the students would increase their vocabulary in order to write more effectively and to generate work that was richer and better.